Method and perspective in anthropology papers in honor of Wilson D. Wallis. - Spencer, Robert F. (University of Minnesota Press, 1954)
Method and Perspective in Anthropology was first published in 1954. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. The boundaries and goals of anthropology are changing and expanding as scholars recognize and pursue wider opportunities for achieving an understanding of the cultural development of man. The range of interests of the discipline as shown in this book embodies such varied fields as archaeology, human geography, linguistics, and the organization of society. With the broadening and deepening of these concerns, those working and studying in the various areas of anthropology have sought more concise methods and more adequate techniques with which to meet increasingly complex problems. This volume of papers, published in honor of a scholar who has himself devoted much effort to the refinement of anthropological methods, represents a long step forward toward the solution of some of the problems of methodology. The contributors are outstanding scholars in cultural anthropology, ethnology, and related fields. The first twelve papers, by as many different authors, present discussions of specific aspects of ethnography, cultural anthropology, prehistory, linguistics, ethnogeography, and sociology. The final paper, by Alfred L. Kroeber, provides a critical summary of the preceding papers. All twelve of the writers answer, in their own way, the questions of how they derive their data, and how they establish their theoretical frame of reference. The contributors are, in addition to Professor Kroeber, Melville J. Herskovits, Sister M. Inez Hilger, Elizabeth Colson, David G. Mandelbaum, Allan R. Holmberg, Robert F. Spencer, Ralph Linton, Erwin H. Ackerknecht, Lloyd A. Wilford, Joseph H. Greenberg, Omer C. Stewart, and Raymond V. Bowers.